The genus Leucophenga (Diptera, Drosophilidae), part V: the mutabilis species group from East Asia, with morphological and molecular evidence - Zhou, Lan; Chen, Hong-Wei (Zootaxa, 2015)
A total of seven known species of the Leucophenga mutabilis species group are resurveyed from the East Asia: L. angusta Okada, 1956; L. bellula Bergroth, 1894; L. magnipalpis Duda, 1924; L. nigripalpis Duda, 1924; L. orientalis Lin & Wheeler, 1972; L. striatipennis Okada, 1989 and L. taiwanensis Lin & Wheeler, 1972. The diagnosis of the mutabilis group is revised, and a key to the seven species of this group is provided. DNA sequences of the mitochondrial COI (cytochrome c oxidase subunit I) gene with BOLD process ID and GenBank accession numbers are provided for these species. The pairwise intra- and interspecific Kimura two-parameter COI distances among the aforementioned seven known species are summarized; and the utility of DNA barcoding in the genus Leucophenga is discussed.